Practice of sleep medicine: sleep disorders in children and adults - Stuck, Boris; Maurer, Joachim T.; Schlarb, Angelika A.; Schredl, Michael; Weeß, Hans-Günter (Springer eBook Collection, 2021)
Chapter 1: Physiology of Normal and Disturbed Sleep -- Chapter 2: Diagnostic Measures -- Chapter 3: Insonmia -- Chapter 4: Sleep-related Breathing Disorders -- Chapter 5: Central Disorders of Hypersomnolence -- Chapter 6: Circadian Rhythm Sleep-Wake Disorders -- Chapter 7: Parasomnia -- Chapter 8: Sleep-related Movement Disorders -- Chapter 9: Isolated Symptoms, Normal Variants and Other Sleep Disorders -- Chapter 10: Secondary Sleep Disorders -- Chapter 11: Sleep Disorders in Children.